The ruins of Managua vieja: the use of expressive photography in urban ethnography. Issue 3 (2nd July 2016) - Kroon, Ann
Abstract : This article proposes a method of conducting urban visual work – a practice-led visual study in which researcher-generated expressive photography explores the 'city-as-archive' (Hetherington 2013) and contributes to the urban visual archive. The photographs used in this article focus upon the social world of material remnants in the setting of the old downtown of Managua, Nicaragua. The aim of the article is four-fold: to suggest the epistemological gains of expressive photography, to discuss the methodology and style, to present the use of these images in an urban visual ethnography of Managua and to address related ethical concerns. Although expressive photographs are used to some extent by scholars, there is a noticeable lack of discussion of the method and empirical examples in urban visual studies. In this article, I propose intentionally using expressive photography to convey the subjective and affective knowledge that is generally not communicated by more conventional, 'realist' documentary visual techniques. Moving into a more explicit conversation of the work process, I point out three arenas for inquiry, for which this method can be useful. I detail my own visual ethnographic practice, and present my primary visual aims in three image clusters: expressive photography in conjunction with historical images, theorising the oscillation between absence and presence and visually interpreting the vernacular design of the ruinscape. The article concludes with a consideration of 'ruin romance' as an ethical concern, as well as some reflections over perceived difficulties in using this method as a means of doing academic research.